Pharmaceutical Chemistry : Drugs and Their Biological Targets - Campos Rosa, Joaquín M. (De Gruyter, 2024)
Pharmaceutical chemistry (PC) represents a dynamic field of research that plays a pivotal role in the development of life-saving pharmaceuticals. PC is a precise science: One needs to rely on the accuracy of previous discoveries that have provided massive amount of precious information and databases as a solid foundation to move forward. PC is also an art where the artist uses a subtle mixture of knowledge, experimental learning, creativity, intuition, boldness, and serendipity to paint the right canvas. Nature often serves as a stimulus for pharmaceutical chemists. Many drugs are derived from natural compounds found in plants, fungi, or microorganisms. Chemists study these natural sources, seeking inspiration to design synthetic molecules that mimic the therapeutic properties of the originals while optimizing their characteristics. Francis Collins, geneticist and expert in the pharmaceutical industry, explains that the molecular cause of 4,000 diseases is no longer a secret to humanity, but there are only treatments available for 250 of them. Therefore, the world requires more professionals who can produce better medicines and solve more needs. For this reason, it is urgent to discover a new system, new drugs, better industrial processes and faster responses for rare and complex diseases. That is the importance and need for more students in love with PC. It is the author's wish that volumes 1 and 2 of this series may serve as motivation for students who intend to get started in the exciting world of drug design, synthesis and development. There is no nobler objective than improving health and quality of life of the human race. The unprecedented increase in human life expectancy, which has almost doubled in a hundred years, is mainly due to drugs and to those who discovered them. It is more important to create awareness in the student that he/she is responsible for his own learning and not simply a passive consumer of information. In this way we will be able to train versatile professionals with an attitude of transformative social change. Drug Design and Action is trated in a separate volume ISBN 978-3-11-131654-3.